ANALYSIS OF THE ROLE OF CIAMIS DPRD WOMEN IN MAKING CHILD-FRIENDLY DISTRICT REGULATIONS - Rudi Salam; Ence Sopyan (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2022)
The research was conducted with the intention of knowing about the dynamics of the female legislators of the Ciamis DPRD in the process of making Regional Regulation (Perda) Number 18 of 2018 concerning Child Friendly Districts (KLA) and analyzing the causes of conflict between each member of the Ciamis DPRD. The method used in this research is qualitative with a case study approach. The technique of collecting data in this research is by means of observation, interviews and collecting documents related to the research topic. This study concludes that the dynamics of women legislators in fighting for the interests of children is by accommodating the draft Local Regulation on KLA in an accommodation compromise. The factions in the Ciamis DPRD fully support the issuance of the Regional Regulation, although the political communication process is still carried out by each faction.